2019
DOI: 10.1037/vio0000231
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of childhood abuse and dating violence victimization among early adolescents from Denmark: A latent class approach.

Abstract: Objective: An emerging body of research has examined patterns of adolescent dating violence (ADV) via person-centered approaches. However, these studies seem limited, as they do not integrate previous victimization as part of the violence typology. The present study explored discrete patterns based on different types of childhood abuse and ADV and the role of differential negative outcomes across these patterns. Method: Data from a large Danish survey on dating violence in early adolescence were used. In total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 87 publications
0
8
0
4
Order By: Relevance
“…In the dating violence literature, one of the most common studied risk factors for perpetration and victimization is exposure to traumatic experiences during childhood [ 23 , 24 ]. First described by Felitti and colleagues in their seminal ACE study of 1998, adverse childhood experiences, or ACEs, encompass three forms of traumatic exposure: abuse, neglect, and household challenges [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the dating violence literature, one of the most common studied risk factors for perpetration and victimization is exposure to traumatic experiences during childhood [ 23 , 24 ]. First described by Felitti and colleagues in their seminal ACE study of 1998, adverse childhood experiences, or ACEs, encompass three forms of traumatic exposure: abuse, neglect, and household challenges [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has provided strong support for social learning theory by demonstrating that experiencing physical abuse is positively associated with adolescents’ violent behavior ( Duman and Margolin, 2007 ; Xia et al, 2018 ; Karsberg et al, 2019 ). For example, by analyzing the data collected from a national sample, Cuartas et al (2020) found that physical punishment strongly predicted adolescents’ delinquent involvement, especially violent offending.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Widom et al(2008) (Baeck JE, 2019). 다수 연구에서 데이트 폭력 피해의 위험 요인으로 반복하여 보고되는 것이 바로 아동기 외상 경험이다 (Gagné et al, 2005;Karsberg et al, 2019). 아동기 외상과 데이트 폭력 피해경험은 다 시 친밀한 파트너 폭력(intimate partner violence)과 가 정폭력(domestic violence)을 유의하게 예측한다 (Gómez, 2010).…”
unclassified
“…친밀한 관계에서 일어나는 폭력의 피해는 생애 전반, 세 대를 걸쳐 반복될 위험성이 높다는 결과가 축적되며 재피 해의 관련 변인을 찾으려는 연구가 많아 이루어지고 있다. 아동기 외상으로 인한 PTSD 증상과 학대의 심각도 (Gobin et al, 2013), 외상 후 부정적 인지 (Park JE et al, 2016), 우울 (Miron et al, 2014), 수치심 (Aakvaag et al, 2019), 관계중독 (Jang SO, 2016), 정서표현양가성(Shon IY et al, 2018), 과도한 음주 (Finkelhor et al, 2007;Karsberg et al, 2019) (Enright, 1996). 용서는 연구자마다 다양하게 정의하고 있지만, 누군가 잘못을 했을 때 그 대상에게 가지는 부정 적 생각, 감정, 행동을 중립을 넘어 긍정적 방향으로 변화 시키는 인지, 정서, 행동적 변화 과정이라는 점은 공통적 이다 (Thompson et al, 2005;Worrington, 2007).…”
unclassified
See 1 more Smart Citation